Geologic Setting of Eclogite-facies Assemblages in the St. Cyr Klippe, Yukon–Tanana Terrane, Yukon, Canada - Petrie, M.; Gilotti, J.; McClelland, W.; van Staal, C.; Isard, S. (Geoscience Canada, 2015)
The St. Cyr area near Quiet Lake hosts well-preserved to variably retrogressed eclogite found as sub-metre to hundreds of metre-long lenses within quartzofeldspathic schist in southcentral Yukon, Canada. The St. Cyr klippe consists of structurally imbricated, polydeformed and polymetamorphosed units of continental arc crust and ultramafic–mafic rocks. Eclogite-bearing quartzofeldspathic schist forms thrust slices in a 30 km long by 6 km wide, northwest-striking outcrop belt. The schist unit comprises metasedimentary and felsic intrusive rocks that are intercalated on the metre to tens of metres scale. Ultramafic rocks, serpentinite and associated greenschist-facies metagabbro form imbricated tectonic slices within the eclogite- bearing quartzofeldspathic unit, which led to a previously held hypothesis that eclogite was exhumed within a tectonic mélange. The presence of phengite and Permian zircon crystallized under eclogite-facies metamorphic conditions in the quartzofeldspathic host rocks indicate that the eclogite was metamorphosed in situ together with the schist as a coherent unit that was part of the continental arc crust of the Yukon–Tanana terrane, rather than a mélange associated with the subduction of oceanic crust of the Slide Mountain terrane. Petrological, geochemical, geochronological and structural similarities link St. Cyr eclogite to other high-pressure localities within Yukon, indicating the high-pressure assemblages form a larger lithotectonic unit within the Yukon–Tanana terrane.